MHC composition of single muscle fibres, sattelite cells and myonuclei in wrestlers - Mandroukas, A.; Metaxas, T.; Christoulas, K.; Vamankudis, E.; Stefanidis, P.; Papavasilou, A.; Kotoglou, K.; Balasas, D.; Heller, J.; Ekblom, B.; Mandroukas, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Few studies have examined the effects of long-term wrestling training on muscle morphology and function (Adams et al., 1993; Tesch and Karlsson, 1985). All the above mentioned studies were conducted more than 20 years ago and they used mATPase staining methodology and not the modern sensitive immunohistochemical analytic method in order to study changes in the patterns of Myosin Heavy Chain (MHC) isoform expression. The aim of this study was to investigate the long-term effects of high intensity resistance wrestling training on MHC isoforms composition, on satellite cells and myonuclei behavior, on embryonic and neonatal MHCs and to compare with untrained subjects. Methods Nine Greco-Roman competitive wrestlers (mean age 20.1±2.7yrs, height 175.0±0.6cm, weight 83.2±12.5kg, yrs of training 7.6±2.7yrs) and six healthy physical education students (mean age 21.2±0.9yrs, height 180.0±0.3cm, weight 80.1±9.4kg) participated in this study. Muscle biopsies were obtained from deltoid muscle in order to investigate muscle fibre distribution, cross sectional area (CSA), single fibres, satellite cells and myonuclei by immunohistochemistry. MHC isoform composition of single fibres was determined with protein electrophoresis. Results: Immunohistochemical analysis showed that muscle fibre distribution of the MHC I and IIA were significantly higher in wrestlers than in students (p<.05). The proportion of MHC IIX was higher by 7% in students compared to wrestlers. Electrophoretic analysis of single muscle fibres revealed a significantly higher proportion of fibres containing MHC I and hybrid fibres containing MHC IIC in wrestlers compared to students (p<.05). However, students displayed a significant higher proportion of MHC IIX compared to wrestlers (p<.001). The mean CSA of type IIA fibres and the number of myonuclei per type II fibres was significantly higher in wrestlers compared to students (p<.05). In wrestlers, myotubes were observed as well as internal nuclei, intermediate and small sized skeletal muscle fibres expressing embryonic and neonatal MHC and none in students. Discussion: The present study revealed that the deltoid muscle of wrestlers contains a larger proportion of fibres with MHC I, IIA and single muscle fibres MHC I and IIC isoforms and very few fibres containing MHC IIX isoforms. Long-term wrestling training may cause hypertrophy especially in MHC IIA, and a transformation of MHC IIX into IIA and IIC of the deltoid muscle. The hypertrophy of MHC IIA seems to be associated with an increase in the number of the myonuclei attached to them and an increase in the number of satellite cells. It is suggested that the observed muscle fibre profile in the